EXPLORING THE BENEFITS OF ENGLISH ENTERTAINMENT EXPOSURE AS LANGUAGE ACQUISITION - muhammad alwi alhadad (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: English proficiency has become significant factor in global communication and development and the widespread of technology increases the exposure of English language. Therefore, it is important to conduct study on how English media and entertainment exposure can promote English language skills. This study conducted using descriptive qualitative method with semi structured interview through WhatsApp voice note on 5 students of English department to identify the benefit of English entertainment such as video, music and English based text on English skills. The results show that all the students give positive responses. It is also confirmed that watching English movies facilitates students with authentic material that develops pronunciation, speaking fluency and listening skills with the help of English subtitles. Regarding to English songs the students mainly benefited through flexibility of using music, repeated words and lyric that promotes listening skills and vocabulary knowledge and retention while English text provides learner with wide array of vocabulary that will help students to develop their vocabulary knowledge and well written language structures and patterns that promotes writing skills and grammar. It is suggested to directs the students to be exposed in English through entertainment outside the class to promote their language skills.Key Words: English Entertainment, Benefits, Language Acquisition